ESTABLISHING AND MAINTAINING CORE INSTRUCTIONAL FRAMEWORKS IN THE KINDERGARTEN THROUGH FIFTH-GRADE ENGLISH LANGUAGE ARTS CLASSROOM - Johnson, Bridget C. (East Carolina University, 2019)
This study presents a problem of practice in the format of a small-scale proof of concept. The topic is focused on a comprehensive process to improve the implementation of K-5 literacy instruction within a rural district of North Carolina. Improvement Science was used to assist in identifying the problem and to create strategies of improvement in the standardization of literacy instruction within the district. Prior to the implementation of this framework of literacy instruction, instructional practices were not specifically enunciated within the school system. In an effort to establish core instruction in a Multi-Tiered System of Support (MTSS), it was necessary to develop common language and clear expectations. This problem of practice outlines not only the initial implementation of the framework, but also the sustainability efforts that were established to aid all teachers and district leaders in fully understanding and teaching with the framework of instruction.
Keywords: Instructional Framework; Core Instruction; Literacy Framework; Literacy programs--North Carolina; Reading--North Carolina; Rural schools--North Carolina